Assembly of the bacterial type III secretion machinery. Issue 4 (17th February 2014) - Diepold, Andreas; Wagner, Samuel
Abstract Many bacteria that live in contact with eukaryotic hosts, whether as symbionts or as pathogens, have evolved mechanisms that manipulate host cell behaviour to their benefit. One such mechanism, the type III secretion system, is employed by Gram‐negative bacterial species to inject effector proteins into host cells. This function is reflected by the overall shape of the machinery, which resembles a molecular syringe. Despite the simplicity of the concept, the type III secretion system is one of the most complex known bacterial nanomachines, incorporating one to more than hundred copies of up to twenty different proteins into a multi‐MDa transmembrane complex. The structural core of the system is the so‐called needle complex that spans the bacterial cell envelope as a tripartite ring system and culminates in a needle protruding from the bacterial cell surface. Substrate targeting and translocation are accomplished by an export machinery consisting of various inner membrane embedded and cytoplasmic components. The formation of such a multimembrane‐spanning machinery is an intricate task that requires precise orchestration. This review gives an overview of recent findings on the assembly of type III secretion machines, discusses quality control and recycling of the system and proposes an integrated assembly model.